Plenasium (Aurealcaulis) elegans sp. nov. from the Eocene of Vietnam – a connecting link in the evolution of modern Royal Ferns (Osmundeae, Osmundaceae). (17th April 2020) - Hiller, P.; Böhme, M.; Schneider, S.; Prieto, J.; Bomfleur, B.
Abstract : Osmundales is the most ancient of all extant groups of leptosporangiate ferns, with an extensive fossil record from Permian to Cenozoic deposits worldwide. The group was particularly diverse during the late Palaeozoic and early Mesozoic, whereas nearly all records of fossil Osmundales from the mid-Cretaceous onwards can be assigned to the sole surviving subfamily Osmundoideae. The single exception has long remained the enigmatic Aurealcaulis – a genus of large, presumably arborescent Osmundaceae stems from the Cretaceous and Palaeogene of North America. Due to similarities especially in the unusual mode of leaf-trace formation, Aurealcaulis has recently been suggested to represent a close relative of modern Plenasium, but definite evidence for this hypothesis has thus far been lacking. Here, we describe Plenasium ( Aurealcaulis ) elegans sp. nov. based on a calcified trunk from the Na Duong Formation (upper middle to upper Eocene) of northern Vietnam, forming the first record of Aurealcaulis outside North America. The new species differs from all previously described members of Aurealcaulis in its uniquely thick xylem siphon and in the characteristic distribution of sclerenchyma in the stipular wings, with a single thick mass surrounded by numerous smaller strands. In its combination of anatomical features, Plenasium elegans appears intermediate between the remaining species of Aurealcaulis and fossil and extant members of Plenasium sensu stricto . Together with its comparatively young geological age and unusual geographical occurrence within the biogeographical range of extant Plenasium species, Plenasium elegans forms a threefold connecting link in the phylogeny of modern Royal Ferns.